2005
DOI: 10.1002/ptr.1528
|View full text |Cite
|
Sign up to set email alerts
|

Oregano and clove essential oils induce surface alteration ofSaccharomyces cerevisiae

Abstract: The antimicrobial properties of volatile aromatic oils have been recognized since antiquity. Oregano and clove oils have been shown to possess a broad spectrum of antimicrobial activity. In this paper, the fungicidal action of these two essential oils was studied on the yeast model Saccharomyces cerevisiae. Yeast cell lysis was shown by the release of substances absorbing at 260 nm. In addition, scanning electron microscopy analyses revealed that the surface of treated cells by oregano and clove oils was signi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
40
1
2

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(47 citation statements)
references
References 16 publications
(17 reference statements)
3
40
1
2
Order By: Relevance
“…The oil is active against oral bacteria associated with dental caries and periodontal diseases [9] and is effective against a large number of other bacteria: Escherichia coli, Salmonella enteric [10] and Staphylococcus aureus [11 -13]. Previous studies have reported antifungal [14], anticarcinogenic [15], antiallergic [8], antimutagenic [16], antioxidant [17] and insecticidal [18,19] properties. The chief constituent of clove oil is eugenol, which is used as a starting material for the production of vanillin [20].…”
Section: Introductionmentioning
confidence: 99%
“…The oil is active against oral bacteria associated with dental caries and periodontal diseases [9] and is effective against a large number of other bacteria: Escherichia coli, Salmonella enteric [10] and Staphylococcus aureus [11 -13]. Previous studies have reported antifungal [14], anticarcinogenic [15], antiallergic [8], antimutagenic [16], antioxidant [17] and insecticidal [18,19] properties. The chief constituent of clove oil is eugenol, which is used as a starting material for the production of vanillin [20].…”
Section: Introductionmentioning
confidence: 99%
“…The oil possesses antibacterial, antifungal, antioxidant and cytotoxic properties (Baratta et al, 1998;Dorman et al, 2000;Gayoso et al, 2005;Prashar et al, 2006;Politeo et al, 2010). Traditionaly for its medicinal properties (treatment of dental care, analgesic and antiseptic etc) (Cai and Wu, 1996), Syzygium aromaticum oil has been demonstrated to be effective in treating antifungal (Chami et al, 2005), antibacterial (Cai and Wu, 1996;Beuchat, 2000;Friedman et al, 2002;Kalemba and Kunicka, 2003), anticarcinogenic (Zheng et al, 1992), antiallergic (Kim et al, 1998), antimutagenic activity (Miyazawa and Hisama, 2001), analgesic, anesthetic, stimulating, stomach ache tonic, antiemetic, antiseptic, antispasmodic (Sellan, 2002;Lavabre, 1992).…”
Section: Introductionmentioning
confidence: 99%
“…This hypothesis is borne out by the work of Bennis and Chami et al [6,7] which shows a similar action of oregano EO and carvacrol on Saccharomyces using a scanning electron microscope (SEM). Moreover, the work of Xing et al [29] shows the action of cinnamaldehyde on hyphae and conidia of Fusarium verticillioides using an SEM and TEM (transmission electron microscope).…”
Section: Effect Of MC On the Destruction Of Fod Conidiamentioning
confidence: 97%
“…Several publications from our laboratory have previously reported in vitro and in vivo antifungal activity of some EOs and their MCs, especially the phenolic compounds such as thymol, carvacrol and eugenol [6][7][8].…”
Section: Introductionmentioning
confidence: 99%